Temporal Patterns of Road Traffic Injuries in Iran - Khorshidi; Ainy; Hashemi Nazari; Soori (Archives of Trauma Research, 2016)

(untitled)
Background Road traffic injuries (RTIs) are the main causes of death and disability in Iran. However, very few studies about the temporal variations of RTIs have been published to date.